IL-23 production in human macrophages is regulated negatively by tumor necrosis factor α-induced protein 3 and positively by specificity protein 1 after stimulation of the toll-like receptor 7/8 signaling pathway. Issue 2 (February 2022) - Yamaguchi, Rui; Sakamoto, Arisa; Yamaguchi, Reona; Haraguchi, Misa; Narahara, Shinji; Sugiuchi, Hiroyuki; Yamaguch, Yasuo
Abstract: The IL-23/IL-17 axis plays an important role in the development of autoimmune diseases, but the mechanism regulating IL-23 production is mainly unknown. We investigated how TNFAIP3 and Sp1 affect IL-23 production by human macrophages after exposure to resiquimod, a TLR7/8 agonist. IL-23 production was significantly upregulated by resiquimod but only slightly by LPS (a TLR4 agonist). Interestingly, IL-23 levels were significantly attenuated after sequential stimulation with LPS and resiquimod, but IL-12p40 and IL-18 levels were not. TLR4-related factors induced by LPS may regulate IL-23 expression via TLR7/8 signaling. LPS significantly enhanced TNFAIP3 and IRAK-M levels but reduced Sp1 levels. After exposure to resiquimod, RNA interference of TNFAIP3 upregulated IL-23 significantly more than siRNA transfection of IRAK-M did. In contrast, knockdown of Sp1 by RNA interference significantly attenuated IL-23 production. Transfection with siRNA for TNFAIP3 enhanced IL-23 expression significantly. After stimulation with resiquimod, GW7647—an agonist for PPARα (an inducer of NADHP oxidase)—and siRNA for UCP2 (a negative regulator of mitochondrial ROS generation) enhanced TNFAIP3 and reduced IL-23. siRNA for p22phox and gp91phox slightly increased Sp1 levels. However, after exposure to resiquimod siRNA-mediated knockout of DUOX1/2 significantly enhanced Sp1 and IL-23 levels, and decreased TNFα-dependent COX-2 expression. Concomitantly, TNFAIP3 levels was attenuated by DUOX1/2 siRNA. TNFAIP3 and Sp1 levels are reciprocally regulated through ROS generation. In conclusion, after stimulation of the TLR7/8 signaling pathway IL-23 production in human macrophages is regulated negatively by TNFAIP3. Abstract : Human macrophage, IL-23, TNFAIP3, IRAK-M, Specificity protein 1.